The Effect of Using Obenkyo Application on the Hiragana Mastery of Students at SMK Negeri 1 Padang Panjang - Kiki Wenisa Putri; Shindu Krisnanda (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2026)
This study was motivated by the low ability of students in reading and writing Hiragana characters and the limited use of interactive learning media at SMK Negeri 1 Padang Panjang. The purpose of this research was to determine the effect of using the Obenkyo application on students’ mastery of Hiragana. This research employed a quantitative approach using a quasi-experimental method with a pre-test post-test control group design. The sample consisted of two classes: XI Hospitality as the experimental group and XI Marketing 1 as the control group, each with 31 students. The research instrument was a written test consisting of multiple-choice and fill-in-the-blank questions. The results showed a significant improvement in the experimental group after using the Obenkyo application. The post-test average score of the experimental group was higher than that of the control group. The t-test revealed a significance value of less than 0.05, indicating that H₀ was rejected and H1 was accepted. Thus, it can be concluded that the use of the Obenkyo application has a significant effect on improving students’ mastery of Hiragana at SMK Negeri 1 Padang Panjang.